P3-S6.02 Is fourfold drop of the nontreponemal antibody titrestitres at three or 6 months after early syphilis treatment an effectiveness "criterion?". (10th July 2011) - Zhou, P; Gu, X; Lu, H; Guan, Z; Qian, Y
Abstract : Background: At present the criteria for treatment effective in early syphilis is the disappearance of clinical symptoms and signs and four-fold decrease of nontreponemal antibody titres within 3 to 6 months after therapy. However, how to evaluate if syphilis is cured after treatment remains difficult and controversial. Methods: Secondary syphilis patients whose rapid plasma reagin (RPR) titres did not turn negative at least 24 months after treatment were enrolled in this study and their CSF were evaluated. The criteria for enrolment were: (1) RPR titres declined fourfold within 3 months after therapy for secondary syphilis; (2) patients denied high risk sexual behaviour following syphilis treatment; (3) RPR titre did not turn negative at least 24 months after treatment; and (4) HIV negative. The criteria for neurosyphilis were: (1) CSF leukocyte count was elevated, and/or (2) proteins were abnormal, and (3) a reactive VDRL-CSF test in the absence of substantial contamination of CSF with blood, and (4) a reactive TPPA-CSF test, and (5) a negative HIV test, and (6) with or without neurological manifestations, and (7) excluding other possible CNS infections. Results: There were 14 male and three female patients who met the criteria for neurosyphilis. The CSF leukocyte count was elevated in 10 patients among which nine also had CSF proteins elevated. The other three patients had CSF proteins elevated only. CSF-VDRL and CSF-TPPA were reactive in all 17 patients. There were four cases presenting notable neurological and psychiatric manifestations, and other 13 had no signs and symptoms of CNS when they entered the study. The clinical symptoms and signs disappeared or improved in four patients, and CSF-WBC in those nine patients turned to normal after treatment. CSF-protein declined accordingly but did not turn to normal in four cases see Abstract P3-S6.02 table 1 . Conclusions: A four-fold decrease in serological titres and resolution of lesions of early syphilis may not predict success. The occurrence of failure after standard therapies suggests that the current criteria for "treatment effective" are questionable. There is a need of continuing to evaluate early syphilis patients who meet the criteria for "treatment effective" and whose nontreponemal antibody titres fail to turn negative afterwards.